2012
DOI: 10.1371/journal.pone.0044145
|View full text |Cite
|
Sign up to set email alerts
|

A Large Insertion in bHLH Transcription Factor BrTT8 Resulting in Yellow Seed Coat in Brassica rapa

Abstract: Yellow seed is a desirable quality trait of the Brassica oilseed species. Previously, several seed coat color genes have been mapped in the Brassica species, but the molecular mechanism is still unknown. In the present investigation, map-based cloning method was used to identify a seed coat color gene, located on A9 in B. rapa. Blast analysis with the Arabidopsis genome showed that there were 22 Arabidopsis genes in this region including at4g09820 to at4g10620. Functional complementation test exhibited a pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 47 publications
8
105
0
1
Order By: Relevance
“…rapa . However, the amounts of mRNA for DFR , anthocyanidin synthase ( ANS ), and anthocyanidin reductase ( ANR ) are not statistically significant in transparent seed coat phenotypes [31]. Arabidopsis thaliana tt3 mutant seeds have transparent seed coats, and visible anthocyanidins or proanthocyanidins are not detected in the tt3 mutant because it lacks DFR mRNA [32].…”
Section: Discussionmentioning
confidence: 99%
“…rapa . However, the amounts of mRNA for DFR , anthocyanidin synthase ( ANS ), and anthocyanidin reductase ( ANR ) are not statistically significant in transparent seed coat phenotypes [31]. Arabidopsis thaliana tt3 mutant seeds have transparent seed coats, and visible anthocyanidins or proanthocyanidins are not detected in the tt3 mutant because it lacks DFR mRNA [32].…”
Section: Discussionmentioning
confidence: 99%
“…S1; Notes S1). Distance analysis revealed that these bHLH transcription factors, including Arabidopsis TT8, BrTT8 (Brassica rapa), are clustered in an AN1/TT8 clade (Li et al, 2012). Less identity was seen with potential monocot orthologs such as maize IN1 and rice Rc (Fig.…”
Section: Identification Of Mttt8 From the M Truncatula Mttt8 Mutantmentioning
confidence: 99%
“…Cs1 excision from Y causes the pericarp to revert to red (Chopra et al, 1999). TE-mediated insertional mutations also cause alterations of seed coat color and flower color in Ipomoea purpurea (Clegg and Durbin, 2000;Park et al, 2007), changes in seed coat color in Brassica rapa , changes in hull and internode color in rice (Hong et al, 2012), and differences in grape skin color (Kobayashi et al, 2004).…”
Section: Te-induced Insertional Mutations Cause Phenotypic Changes Inmentioning
confidence: 99%